Evaluation of PM2.5 air pollution sources and cardiovascular health. Issue 3 (20th June 2021) - Slawsky, Erik; Ward-Caviness, Cavin K.; Neas, Lucas; Devlin, Robert B.; Cascio, Wayne E.; Russell, Armistead G.; Huang, Ran; Kraus, William E.; Hauser, Elizabeth; Diaz-Sanchez, David; Weaver, Anne M.
Abstract : Supplemental Digital Content is available in the text. Abstract : Long-term air pollution exposure, notably fine particulate matter, is a global contributor to morbidity and mortality and a known risk factor for coronary artery disease (CAD) and myocardial infarctions (MI). Knowledge of impacts related to source-apportioned PM2.5 is limited. New modeling methods allow researchers to estimate source-specific long-term impacts on the prevalence of CAD and MI. The Catheterization Genetics (CATHGEN) cohort consists of patients who underwent a cardiac catheterization at Duke University Medical Center between 2002 and 2010. Severity of coronary blockage was determined by coronary angiography and converted into a binary indicator of clinical CAD. History of MI was extracted from medical records. Annual averages of source specific PM2.5 were estimated using an improved gas-constrained source apportionment model for North Carolina from 2002 to 2010. We tested six sources of PM2.5 mass for associations with CAD and MI using mixed effects multivariable logistic regression with a random intercept for county and multiple adjustments. PM2.5 fractions of ammonium bisulfate and ammonium nitrate were associated with increased prevalence of CAD (odds ratio [OR] 1.20; 95% CI = 1.11, 1.22 and OR 1.18; 95% CI = 1.05, 1.32, respectively). PM2.5 from ammonium bisulfate and ammonium nitrate were also associated with increased prevalence of MI (OR 1.20; 95% CI = 1.10, 1.29 and OR 1.35; 95% CI = 1.20, 1.53, respectively). Greater PM2.5 concentrations of ammonium bisulfate and ammonium nitrate are associated with greater MI and CAD prevalence. The association with bisulfate suggests aerosol acidity may play a role. Our findings suggest analyses of source specific PM2.5 mass can reveal novel associations.